2014
DOI: 10.3892/mco.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking and alcohol consumption on 5-fluorouracil-related metabolic enzymes in oral squamous cell carcinoma

Abstract: Abstract. Lifestyle, particularly smoking and alcohol consumption, may induce and/or inhibit drug metabolism. In order to reveal the effects of smoking and alcohol consumption on the 5-fluorouracil (5-FU)-related metabolic enzymes, namely thymidylate synthase, dihydropyrimidine dehydrogenase (DPD; a sole catabolic enzyme of 5-FU), orotate phosphoribosyl transferase (OPRT) and thymidine phosphorylase, in oral squamous cell carcinomas, the mRNA expression of these enzymes was investigated in 29 surgical specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, p21 overexpression was found to be associated with poor prognosis, specifically in the operable ESCC patients. Moreover, Yamashita et al [ 33 ] revealed that smoking might vary the activity of the 5-FU-related metabolic enzymes, resulting in poor curative effect. 5-Fluorouracil (5-FU) is an anticancer agent widely used in the treatment of digestive tract tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p21 overexpression was found to be associated with poor prognosis, specifically in the operable ESCC patients. Moreover, Yamashita et al [ 33 ] revealed that smoking might vary the activity of the 5-FU-related metabolic enzymes, resulting in poor curative effect. 5-Fluorouracil (5-FU) is an anticancer agent widely used in the treatment of digestive tract tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, smoking may reduce the anticancer activity of 5-FU, possibly through the induction of dihydropyrimidine dehydrogenase activity, which is the initial and rate-limiting enzyme in the catabolic pathway of 5-FU. 42 Moreover, smoking contains thousands of different compounds, which have carcinogenic activity. 43 Another interesting finding in the current study was shown in CRC patients with baseline over-expression with EGFR, in them the combination of COX2 with other cytokines expression levels generated a significant inflammation index for the prediction of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, smoking may reduce the anticancer activity of 5-FU, possibly through the induction of dihydropyrimidine dehydrogenase activity, which is the initial and rate-limiting enzyme in the catabolic pathway of 5-FU. 42 Moreover, smoking contains thousands of different compounds, which have carcinogenic activity. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke exerts inflammatory and suppressive effects on immune cells, alters mucosal immunity and promotes autoimmunity, resulting in oral cancers [10]. Yamashita et al [11] found that smoking and drinking can inhibit 5-fluorouracil (5-FU)-related metabolic enzymes through the induction of dihydropyrimidine dehydrogenase (DPD; a sole catabolic enzyme of 5-FU) activity, which in turn lead to oral cancers. In addition, alcohol consumption can interact with the polymorphisms of ALDH2 and CYP2E1-RsaI genes to increase OSCC risk [12].…”
Section: Introductionmentioning
confidence: 99%